Determinants of economic growth in East African countries: A dynamic panel model approach - Muuz Hadush; Kidanemariam Gebregziabher; Sisay Biruk (Cogent Economics & Finance, 2023)
The purpose of this study is to analyze the determinant of economic growth in the region of East African countries from 2002 to 2018. In order to investigate empirically the key determinants of economic growth in East African countries, this study used a dynamic panel model. To improve efficiency, Generalized Moments Method (GMM) estimators are used. Based on panel data from the East African countries during the 2002-2018 period, this study, therefore, estimated the determinants of economic growth in the region. The result suggests that government expense, government revenue, volume of imports and exports of goods and services significantly contribute to the economic growth of the countries. However, the consumer price index, current account balance, gross government debt, and foreign direct investment lead to negative economic growth. The paper has three policy implications; first, promoting open trade and ensuring peace and stability in the region is a paramount policy to enhance the economic growth of the region. East African Countries should move forward in creating stability regionally and internally within the countries. Second, countries in East Africa are recommended to strengthen and sustain their policies on government expenses, government revenue and revise their policies on government debt, inflation and current account balance. Major reforms are required in foreign direct investment and general government debt within the region. Third, to address obstacles in trade, climate change and the tax collection system, political and economic integration is fundamental to the region and to making the region competitive in the international trade arena.
Keywords: 330; determinants; dynamic mode; East African countries; economic growt; generalized moments methods; gross domestic product